2022
DOI: 10.5194/gmd-15-6143-2022
|View full text |Cite
|
Sign up to set email alerts
|

Simulations of aerosol pH in China using WRF-Chem (v4.0): sensitivities of aerosol pH and its temporal variations during haze episodes

Abstract: Abstract. Aerosol pH is a fundamental property of aerosols in terms of atmospheric chemistry and its impact on air quality, climate, and health. Precise estimation of aerosol pH in chemical transport models (CTMs) is critical for aerosol modeling and thus influences policy development that partially relies on results from model simulations. We report the Weather Research and Forecasting Model coupled with Chemistry (WRF-Chem) simulated PM2.5 pH over China during a period with heavy haze episodes in Beijing, an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 100 publications
(144 reference statements)
0
0
0
Order By: Relevance
“…Subsequently, the Multi-resolution Emission Inventory (MEIC, http://meicmodel.org.cn) covered mainland China (Li et al, 2017;Zheng et al, 2018). Previous studies indicated that bottom-up emission inventories may underestimate NH3 emissions in northern China by approximately 40% (Zhang et al, 2018;Wang et al, 2018;Kong et al, 2019;Ruan et al, 2022). Hence, NH3 emissions for the North China Pain region were multiplied by a factor of 1.4.…”
mentioning
confidence: 99%
“…Subsequently, the Multi-resolution Emission Inventory (MEIC, http://meicmodel.org.cn) covered mainland China (Li et al, 2017;Zheng et al, 2018). Previous studies indicated that bottom-up emission inventories may underestimate NH3 emissions in northern China by approximately 40% (Zhang et al, 2018;Wang et al, 2018;Kong et al, 2019;Ruan et al, 2022). Hence, NH3 emissions for the North China Pain region were multiplied by a factor of 1.4.…”
mentioning
confidence: 99%